ANALISIS PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PT SURGANYA MOTOR INDONESIA BANDUNG - Mariati Tirta Wiyata; Hasti Pramesti Kusnara (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The Effect of Promotion and Price on Consumer Purchase Decisions on motorcycle spare parts (two wheels). This study aims to assess how much influence promotion and price have on consumer purchasing decisions at PT Surganya Motor Indone;’l;[sia Bandung. The type of research used is quantitative explanatory research. The processed data is the result of distributing questionnaires to customers of PT Surganya Motor Indonesia Bandung. The data analysis technique used in this research is multiple linear regression. To explain the description of research related to the hypothesis by using the following analysis: Validity Test, Reliability Test, t Test (Partial). on Consumer Purchase Decisions.